Complement 9 in amyloid deposits - Lux, Annelie; Gottwald, Juliane; Behrens, Hans-Michael; Daniel, Christoph; Amann, Kerstin Ute; Roecken, Christoph (Amyloid-Journal of Protein Folding Disorders, 2021)
Amyloidosis is a disease group caused by pathological aggregation and deposition of peptides in diverse tissue sites. Apart from the fibril protein, amyloid deposits frequently enclose non-fibrillar constituents. In routine diagnostics, we noticed the presence of complement 9 (C9) in amyloid. Based on this observation, we systematically explored the occurrence of C9 in amyloid. Apolipoprotein E (apoE), caspase 3 and complement 3 (C3) served as controls. From the Amyloid Registry Kiel, we retrieved 118 formalin-fixed and paraffin-embedded tissue samples, including eight different amyloid- and 18 different tissue types. The expression patterns were assessed immunohistochemically in relation to amyloid deposits. A literature search on proteomic data was performed. Amyloid deposits stained for C9 and apoE in 117 (99.2%) and 112 of 118 (94.9%) cases, respectively. A homogeneous immunostaining of the entire amyloid deposits was found in 75.4% (C9) and 61.9% (apoE) of the cases. Caspase 3 and C3 were present only in 22 (19.3%) of 114 and 20 (36%) of 55 assessable cases, respectively. Caspase 3 and C3 immunostaining rarely covered substantial areas of the amyloid deposits. The literature search on proteomic data confirmed the frequent detection of apoE and the occurrence of C9 and C3 in amyloid deposits. No data were found regarding caspase 3. Our findings demonstrate the ubiquitous, spatial and specific enrichment of C9 in amyloid deposits irrespective of amyloid-, organ- or tissue type. Our findings lend support to the hypothesis that amyloidosis might activate the complement cascade, which could lead to the formation of the membrane attack complex and cell death.
CRIS-Team WoS Importer:2021-06-11